Southern Iberia in the early Iron Age - Morgenroth, U; Ulrich Morgenroth (1999)
﻿ During the first half of the 8th century, people from the Phoenician Levant came to southern Iberia and founded a chain of settlements along the Spanish Mediterranean coast, as well as the city of Gadir (modern Cadiz) on the Atlantic seaboard. It is generally agreed that these colonisers came to the region to exploit the rich deposits of precious metals. Oriental style objects, which indicate the exchange between the Phoenician settlers and indigenous communities, can be found in almost all indigenous early Iron Age sites in the region. Initially, the purpose of this study had been to detect the elements of Greek and Phoenician influence in the material culture of the early Iron Age (the 8th century until around 600 BC), but as work progressed it became increasingly clear that this undertaking was far more complex than it had been assumed. The Phoenicians turned out to be only one factor in a complex process of transformation from the late Bronze Age way of life to the development of the early Iberian states after 600 BC. While the examination of the interaction between the indigenous communities and the eastern Mediterranean colonisers remained an important part of the study, my investigation now attempts to generate a more general picture of the early Iron Age in modern Andalusia, including the analysis of the social and economic processes which transformed society throughout the period. The investigation is organised on the basis of three major parts: An introduction: including the geography and climate of the region, as well as the history and archaeology of the Pheonician colonisation (with a certain emphasis on Gadir, and the excellently excavated site of Castillo Doña Blanca); as well as the indigenous Bronze Age background, and a number of theoretical considerations. The central part introduces the archaeological evidence, organised in two sections: a topographical section, describing the settlement and cemetery evidence; and a second section, discussing a selection of artefacts which, in my opinion, are particularly useful for a reconstruction of the social processes. Finally, the synthesis attempts to reconstruct various aspects of the early Iron Age culture in the region: such as the economic organisation, social development, ritual practice, and significance of the Phoenician presence for the development of the local cultures, as well as to introduce a regional division of the area under discussion.